EFFECTIVE WAYS OF USING PICTURES IN TEACHING GRAMMAR FOR YOUNG LEARNERS - Toshboltayeva Sabrina; Ruziyeva Shahribonu (Ustozlar uchun, 2025)
Teaching grammar to young learners presents a unique set of challenges due to their cognitive development and limited abstract thinking abilities. Visual aids, particularly pictures, have proven to be highly effective in enhancing grammar instruction. This article explores various methodologies for integrating pictures into grammar teaching, supported by educational theories and practical classroom applications. The use of visuals not only simplifies grammatical structures but also fosters motivation, engagement, and long-term retention.